STUDENTS’ RESPONSES TOWARD LEARNING READING DESCRIPTIVE TEXT USING TEAMS GAMES TOURNAMENT (TGT) METHOD - Habsoh, Siti; Resmini, Setya (IKIP Siliwangi, 2022)
Reading is one of four skills that should be learned by the students to master a language because reading can give many information contained in the text to the reader. There are so many students who do not master in reading skill because of some factors such as lack of motivation and monotonous class activity. TGT method is part of cooperative learning that can help students to improve their reading skill. The objective of this research is to indentify the students’ responses toward TGT method in learning reading skill. The research uses descriptive qualitative design with 31 of seventh grade students as participants. The instruments of this research are questionnaire, interview and observation sheet. The result of data analysis shows that students give various responses toward TGT method, both positive and negative, such as TGT method helps them to be more active to participate in the class while the other students think that TGT method makes them confused. Keywords: Teams Games Tournament (TGT), Students’ Responses